Comparison of mouse ovarian follicular development and gene expression in the presence of ovarian tissue extract and sodium selenite: An experimental study - Hamed Shoorei; Mina Jafarabadi; Shahram PourBayranvand; Mojdeh Salehnia (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: Ovarian tissue extract (OTE) and sodium selenite (SS) enhance the growth and maturation of preantral follicles in a dose-dependent manner. Objective: The present study was designed to bring more information regarding the mechanism of OTE and SS on the mRNA expression of follicle-stimulating hormone receptors (FSHR) and the proliferation cell nuclear antigens (PCNA) of in vitro matured isolated follicles. Materials and Methods: The tissue extract was prepared from adult ovaries. The preantral follicles (n = 266) were isolated from 12-16-day-old mice and cultured in the control, experimental I (10 ng/ml SS), and experimental II (OTE) groups for 12 days. The follicular diameter, survival, and maturation rates, also, the production of 17-β-estradiol and progesterone, and the follicular expression of PCNA and FSH receptor genes were analyzed. Results: The survival rate of follicles in the SS-treated group (84.58%) was significantly higher than that OTE (75.63%; p = 0.023) and control (69.38%; p = 0.032) groups. The mean diameter of culture follicles in experimental group I (403.8 μm) and experimental group II (383.97 μm) increased significantly in comparison with the control group (342.05 μm; p = 0.032). The developmental rate of follicles, percentages of antrum formation, released metaphase II oocytes (p = 0.027; p = 0.019 respectively), production of hormones and the expression of 2 studied genes were significantly increased in both experimental groups in compare with control group (p = 0.021; p = 0.023 respectively). Conclusion: The OTE and SS have a positive effect on development of mouse preantral follicles via over-expression of FSHR and PCNA genes.